2021
DOI: 10.1021/acsnano.0c06814
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Determines the Shape of Supraparticles in Self-Lubricating Ternary Droplets

Abstract: Supraparticles are large clusters of much smaller colloidal particles. Controlling the shape and anisotropy of supraparticles can enhance their functionality, enabling applications in fields such as optics, magnetics, and medicine. The evaporation of self-lubricating colloidal ouzo droplets is an easy and efficient strategy to create supraparticles, overcoming the problem of the “coffee-stain effect” during drop evaporation. Yet, the parameters that control the shape of the supraparticles formed in such evapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 61 publications
(148 reference statements)
3
57
0
Order By: Relevance
“…Details of the experimental setup can be found in Raju et al 12 In short, the evaporating droplets were observed from the side using monochrome 8-bit CCD camera and from the top using a CMOS color camera. Both cameras were connected to a Navitar 12X adjustable zoom lens.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the experimental setup can be found in Raju et al 12 In short, the evaporating droplets were observed from the side using monochrome 8-bit CCD camera and from the top using a CMOS color camera. Both cameras were connected to a Navitar 12X adjustable zoom lens.…”
Section: Methodsmentioning
confidence: 99%
“…colloidal Ouzo droplets, is an efficient route to produce supraparticles. 11 , 12 Although it is known that the surface properties of colloidal particles can influence their assembly in droplets, 13 , 14 the role of the particles’ surface on the formation of supraparticles in Ouzo droplets is still unknown. Here we show that the surface properties of the colloidal particles affect and can even impede the formation of supraparticles in colloidal “Ouzo” droplets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supraparticles are finite assemblies of primary colloidal particles with micron-scale dimensions fabricated by confined self-assembly processes, for example, within emulsion droplets. 1 4 If the primary particles are sufficiently monodispersed, such supraparticles exhibit a well-defined structural order determined by the interplay between the curvature imposed by the templating droplet, 5 7 the system size, 8 , 9 and the shape of the primary particle, 10 12 as well as the drying kinetics. 13 , 14 As inherently hierarchical materials, supraparticles bridge the microscopic and macroscopic scales and combine emergent properties arising from the collective behavior of the primary building blocks with characteristics of a macroscopic powder and finite properties that can be different from self-assembled materials in the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Supraparticles are finite assemblies of primary colloidal particles with micron-scale dimensions fabricated by confined self-assembly processes, for example, within emulsion droplets. If the primary particles are sufficiently monodispersed, such supraparticles exhibit a well-defined structural order determined by the interplay between the curvature imposed by the templating droplet, the system size, , and the shape of the primary particle, as well as the drying kinetics. , As inherently hierarchical materials, supraparticles bridge the microscopic and macroscopic scales and combine emergent properties arising from the collective behavior of the primary building blocks with characteristics of a macroscopic powder and finite properties that can be different from self-assembled materials in the bulk. The size of the primary colloidal particles can be chosen to match the wavelengths of visible light, , in which case the defined structural arrangement in the supraparticles produces tunable structural color with an isotropic or anisotropic appearance. The latter depends on whether their internal structure is amorphous, partially crystalline, or completely crystalline .…”
Section: Introductionmentioning
confidence: 99%